The Development of Business Strategy and Business Model of Sushi Haikara - Rachman, Friza Yuniva; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
The growth of food and beverage industry in Indonesia is rampant. It can be seen from the growth in the culinary industry with a number of people who engaged in this industry and sell any kind of foods. One kind of food which is grown today is Japanese food, especially sushi. The numbers of sushiÃ¢â‚¬â„¢s outlets that offer sushi with high prices without focusing on quality encourage the emergence of sushiÃ¢â‚¬â„¢s outlets that offer medium prices without neglecting the quality of sushi. By looking at these opportunities, Sushi Haikara tries to offer sushi with medium price and high quality. As a start-up business, Sushi Haikara faces some issues as well as challenge in operating the business. It still does not have strong brand awareness and business model yet to focus on its position, concept, and make its brand well-known to the public; as well as develops strategy for the future. This final project focuses on improving business strategy for Sushi Haikara using three business strategies in order to solve the issues and challenge, as well as prepare development strategy for the future of this business. In order to be able to develop the business, Haikara should improve and strengthening its brand, so that public know the presence of this brand, by improving products (both in quality and taste), services, employees, and all aspects which are needed for supporting the business. After focusing on strengthening its brand, Haikara could continue the planning of business development, one of those is by opening branch in other areas. Those strategies as the solutions should be balanced with good implementation, which needs to be applied systematically. It is divided into short-term and long-term plan. The aspects that should be considered for implementation, consists of human resources, marketing and promotion, operational, and financial. Those aspects are very crucial for the business process and need to be improved in order to survive in the industry and develop its business.Ã‚Â Key Words: Business Strategy, Business Model, Japanese Food